1994
DOI: 10.1111/j.1532-5415.1994.tb06502.x
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric Home Assessment After Hospital Discharge

Abstract: Post-discharge visitation by a GNP to patients at high risk is capable of detecting a high yield of important and potentially reversible clinical problems. This multidisciplinary approach is acceptable to physicians. Research is needed to identify additional links between short hospital stays, impairment or instability at discharge, and adverse outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 17 publications
1
27
0
1
Order By: Relevance
“…80 Home visits enable a patient's daily needs and safety (eg, fall risk) to be assessed. They can also be a means of assessing medication safety and adherence by reviewing all prescription and over-the-counter products in the household.…”
mentioning
confidence: 99%
“…80 Home visits enable a patient's daily needs and safety (eg, fall risk) to be assessed. They can also be a means of assessing medication safety and adherence by reviewing all prescription and over-the-counter products in the household.…”
mentioning
confidence: 99%
“…Lack of good discharge instruction results in polypharmacy and readmission as shown in studies. 4,5 Incomplete reporting of laboratory tests and results is also a concern as it may cause duplication of the test that has already been performed when patients comes for follow up.…”
Section: Resultsmentioning
confidence: 99%
“…A seniors center chronic illness self management and disability prevention program managed by a geriatric nurse practitioner indicated that these interventions contributed not only to reductions in functional decline but also to associated reductions in hospital admissions and the number of inpatient days (Leveille, et al, 1998). An additional study by Kravitz, et al (1994) provided specific insights into the spectrum of significant problems identified during home assessments by gerontologic nurse practitioners in which ninety nine percent of patients discharged home from hospital were determined to have new or worsening problems. The authors do state that "more research is needed to identity additional links between short hospital stays, impairment or instability at discharge, and adverse outcomes" (Kravitz, 1994(Kravitz, , p. 1229 however, this research does give an indication of the value of early in-home follow-up after discharge home from hospital as it can be surmised that through the nurse practitioners early interventions, subsequent hospital admissions were prevented.…”
Section: Synthesis Of the Research For Health Status/functional Capacitymentioning
confidence: 99%
“…This search strategy derived nineteen articles of which twelve articles were determined to be appropriate in an attempt to address the question of inquiry set forth in this paper. These twelve articles include one systematic review (Van Haastregt, Diedericks, van Rossum, de Witte, Crebolder, 2000), two meta-analyses (Ploeg et al, 2005;Stuck & Siu, 1993), one combined systematic review and meta-analysis (Elkan et al, 2001 ), five randomized control trials (Leveille, et al , 1998;Sledge et al, 2006;Stuck, et al, 1995;and Stuck et al, 2000;Zimmer, Groth-Juncker, & McCusker, 1985) and three variations of randomized control trials (Bula et al, 1999;Kravitz, et al, 1994;and Naylor & McCauley, 1999). It was noted that the randomized control trial conducted by Levielle, et al (1998) was utilized in the meta-analysis conducted by Ploeg, et al (2005).…”
Section: Sources and Search Processmentioning
confidence: 99%
See 1 more Smart Citation